Role of Zoo-Housed Animals in the Ecology of Ticks and Tick-Borne Pathogens—A Review - Johana Hrnková; Irena Schneiderová; Marina Golovchenko; Libor Grubhoffer; Natalie Rudenko; Jiří Černý (Pathogens, 2021)
Ticks are ubiquitous ectoparasites, feeding on representatives of all classes of terrestrial vertebrates and transmitting numerous pathogens of high human and veterinary medical importance. Exotic animals kept in zoological gardens, ranches, wildlife parks or farms may play an important role in the ecology of ticks and tick-borne pathogens (TBPs), as they may serve as hosts for local tick species. Moreover, they can develop diseases of varying severity after being infected by TBPs, and theoretically, can thus serve as reservoirs, thereby further propagating TBPs in local ecosystems. The definite role of these animals in the tick–host-pathogen network remains poorly investigated. This review provides a summary of the information currently available regarding ticks and TBPs in connection to captive local and exotic wildlife, with an emphasis on zoo-housed species.